Intercalation of catalytically active metal complexes in phyllosilicates and their application as propene polymerisation catalysts - Tudor, J; Willington, L; OHare, D; Royan, B (1996)
The cationic Ziegler-Natta polymerisation catalyst [Zr(η-C5H5Me(thf)]+, is intercalated in a synthetic fluorinated mica-type silicate (NaMg2.5Si4O10F2) and the modified, swelling synthetic hectorite [LaponiteRD, Na0.46Mg5.42Li0.46Si8(OH) 4O20], by ion-exchange of [Zr(η-C5H5Me(thf)]+ ions with the interlamellar cations of the layered silicates; in the presence of methylalumoxane {MAO, (MeAlO)n} these organometallic intercalation compounds are active catalysts for the polymerisation of propene giving low molecular mass atactic polypropylene with a narrow molecular mass distribution. † D. O'Hare is the Royal Society of Chemistry Sir Edward Frankland Fellow.